The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.37689/acta-ape/2020ao02676
|View full text |Cite
|
Sign up to set email alerts
|

Coordenação do cuidado às pessoas que vivem com HIV no sistema prisional

Abstract: Coordenação do cuidado às pessoas que vivem com HIV no sistema prisional Coordination of care for people living with HIV in the prison system Coordinación del cuidado a las personas que viven con el VIH en el sistema penitenciario

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although the prison unit is a favorable environment for DOT, it is worth reflecting on the difficulties involved in complying with the proposal, namely: occupation above its capacity and with no adequate professional sizing (55)(56) ; supremacy of actions aimed at the security/surveillance of inmates and prison professionals to the detriment of actions aimed at health, which prevents the daily attendance of inmates in prison health units for such supervision and limits the access of healthcare professionals to cells and pavilions (55,57) ; penitentiary health agents participate in the regulation of access to health actions without adequate knowledge to do so (58) .…”
Section: Medicalmentioning
confidence: 99%
“…Although the prison unit is a favorable environment for DOT, it is worth reflecting on the difficulties involved in complying with the proposal, namely: occupation above its capacity and with no adequate professional sizing (55)(56) ; supremacy of actions aimed at the security/surveillance of inmates and prison professionals to the detriment of actions aimed at health, which prevents the daily attendance of inmates in prison health units for such supervision and limits the access of healthcare professionals to cells and pavilions (55,57) ; penitentiary health agents participate in the regulation of access to health actions without adequate knowledge to do so (58) .…”
Section: Medicalmentioning
confidence: 99%
“…Regarding the performance of the prison units, studied by Cadamuro et al (2020), all need to improve their performance with regard to the development of actions to monitor the use of ART (Antiretroviral Therapy), inform and discuss test results with inmates and take them to care outside the prison unit, as reported by Ravanholi et al (2019) reported, highlighting the need for prison health teams to conduct actions aimed at monitoring the regularity of ART use in the logic of the cascade of care, supporting subjects to retain care and resulting in clinical improvement and viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the prison population exceeds 800,000, with 392 incarcerated people per 100,000 population (10,11). With the prevalence of diseases, mainly sexually transmitted infections (STIs) and tuberculosis, health in prison settings has become a public health emergency (12)(13)(14)(15). Therefore, several strategies and public policies directed at the prison system were adopted in order to tackle this public health crisis in the country.…”
Section: Introductionmentioning
confidence: 99%